(untitled) (Research, Society and Development, 2022)
Mini-implants can be used in various clinical situations in orthodontics. It is a very satisfactory anchorage treatment alternative, not requiring the direct collaboration of the patient, reducing treatment time, in addition to enabling safe mechanics. The proper installation of the mini-implant will depend on the planning of the clinical case. The objective of this work is to address in which clinical situations the mini-implant should be used, since it is capable of assisting in the treatment of several cases in orthodontics. The search strategy consisted of consulting electronic databases: PubMed, SciELO, LILACS and gray literature (Google Academic). Among the various clinical applications of the mini-implant, we can mention: retraction of anterior teeth, distalization of molars, mesialization of molars, intrusion of posterior and anterior teeth; leveling of the occlusal plane, traction of impacted teeth and correction of posterior crossbite. It is concluded that the mini-implant is an effective maneuver that allows the orthodontist to resolve several treatments.